Healthy eating habits and a prudent dietary pattern improve Nanjing international students’ health-related quality of life - Walker, Anita Nyarkoa; Weeto, Makhala Mary; Priddy, Christiana Babymay; Yakubu, Salimata; Zaitoun, Margaret; Chen, Qianfeng; Li, Bohan; Feng, Yucong; Zhong, Yuxia; Zhang, Yuandie; Wei, Tao; Bafei, Solim Essomandan Clémence; et al. (Frontiers in Public Health, 2023)
Purpose Low-quality dietary practices, such as fast food consumption and skipping meals, deteriorate the quality of life. However, the available studies on diet and health-related quality of life (HRQoL) used matrices not specific to nutrition. Moreover, how diet affects the HRQoL of international students in China is unknown. Therefore, using a cross-sectional study, the effect of dietary patterns and habits on the HRQoL of international students in Nanjing, China, was examined. Methods The researchers collected dietary data using a food frequency questionnaire (FFQ) from February to March 2022. Then, the Food Benefit Assessment (FBA) was used to access HRQoL. Finally, the effect of eating habits and dietary patterns on HRQoL was explored using multilinear regression. Results Approximately 454 responses were obtained, with the responses mostly from male subjects (56.4%) and those aged 26 years and above (75.6%). The quality of life according to the food consumed was about average for all the constructs except for aesthetics and disease prevention, as 65.8% skipped meals, particularly breakfast (47.8%). Furthermore, three dietary patterns were identified: prudent, Western, and animal protein patterns. Consequently, by skipping breakfast, vitality (β = −2.362, p = 0.04), wellbeing (β = −3.592, p = 0.007), digestive comfort (β = −4.734, p = 0.008), and disease prevention (β = −5.071, p = 0.031) were all reduced. However, consuming at least three meals daily enhanced vitality (β = 2.254, p = 0.003) and disease prevention (β = 4.441, p = 0.019). Furthermore, aesthetics (β = 4.456, p = 0.05), physical appearance (β = 5.927, p = 0.003), and vitality (β = 3.323, p = 0.009) were also significantly increased by healthy dietary patterns. However, a more Westernized diet led to frequent snacking (β = −4.631, p = 0.032), a decline in wellbeing (β = −5.370, p < 0.001), and discomfort with digestion (β = −5.101, p = 0.01). Finally, increased frequency of snacking (β = −6.036, p = 0.012), a decrease in wellbeing (β = −4.494, p = 0.004), digestive comfort (β = −9.940, p < 0.001), physical appearance (β = −4.926, p = 0.027), and disease prevention (β = −5.835, p = 0.043) were all associated with an increase in animal protein patterns. Conclusion This research indicates that healthy eating habits and patterns positively impact international students’ HRQoL. Therefore, the appropriate authorities should advise students to consume healthy foods regularly to improve their HRQoL.